Policies for industrial development, international collaboration and technological sovereignty: Implications for emerging economies - Henning Kroll (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2024)
This short position paper introduces the concept of technological sovereignty in development as a guiding notion for future-oriented industrial development policy (Lee et al. 2023), derived from the current leading economy discourse on technological sovereignty. That concept suggests that the ambition of all countries should be to develop and retain a combination of own strengths and broad-based international collaboration. It posits that to improve the well-being of their constituency and to develop their industries' capacities to meet global standards, governments need to reinforce domestic capacities and at the same time benefit from external sourcing (Edler et al. 2020). In doing so, this paper underlines that the adequate balance between both efforts will depend on the ambition pursued. While, in a world of increasing geopolitical uncertainty (Acharya 2017; Brewster 2018; Hearson et al. 2018; Khandelwal 2020; Krapohl et al. 2021) and an increasing importance of power-play (Stiglitz et al. 2024), national security concerns may at times justify addressing issues exclusively on home soil, economic concerns will in the vast majority of cases continue to justify international outreach and global collaboration. This holds true with a view to cost considerations and even more so with a view to the sourcing of existing solutions and knowledge. As long as onesided dependencies can be avoided (Edler et al. 2020) and countries do not come to unduly rely on the stability of single political relations, it thus endorses rather than question the established paradigm that economic development requires cooperation rather than autarky. Against this background, technological and economic sovereignty are defined as the ability of a country to develop and retain an independent agency in order to determine its own pathway to develop free of external constraint - without necessarily possessing all capacities itself (Edler et al. 2023; March et al. 2023). In more concrete terms, to develop a capacity of supporting its firms in assuming favourable positions within international value chains - through both domestic capacity building and the conscious management of international relations in science, technology and trade (Gereffi et al. 2013; Henderson et al. 2002; Kano et al. 2020; Yeung 2021). In that sense, discourses at the European level also speak of strategic autonomy, instead of technological sovereignty. (...)
Keywords: 330; Policies; Industrial Development; Implications for Emerging Economies